Performance and Gaseous Emission Investigation of Low Powered Spark Ignition Engine Fueled with Gasoline and Hydroxyl Gas: Hydroxyl Gas-gasoline Mixture Engine - Abbas, Naseem; Badshah, Mohsin Ali; Awan, Muhammad Bilal; Zahra, Nida (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Hydroxyl gas (HHO) has recently been familiarized to the auto energy sector as a new source of energy. The objective of this work was to investigate a simple HHO and gasoline engine to evaluate the effect of hydroxyl gas addition, as an engine performance improver, into gasoline fuel on engine performance and emissions. HHO is a mixture of mono-atomic oxygen (O) and di-atomic hydrogen (H2) that is produced by electrolyzed conversion of water (H2O) in the presence of an active catalyst. Due to high reactive and burning property, it increases the combustion efficiency of gasoline engine when mixed and burnt with gasoline fuel. The HHO gas kit was installed with internal combustion engine, performance analysis and emission analysis has been done by using gasoline and gasoline-HHO separately on the engine. Furthermore, the CO, HC, CO2 and NOx emissions were measured using exhaust gas analyzer (EMS5002). Furthermore, the effect of HHO co-burning with gasoline on engine efficiency and environment are discussed. An Experimental investigation is conducted on a 70-cc, four strokes, air cooled, single cylinder internal combustion engine. After investigation, the Engine power was enhanced by approximately 12.2% with significant reduction of specific fuel consumption (SFC) by approximately 37.5% and overall efficiency (ɳo) has been increased to 41.5%. Furthermore, unburnt HC concentrations, CO2, CO and NOx have been reduced by approximately 39.9%, 38%, 53% and 21% respectively.